Effect of thermomechanical treatment and length-scales on spatial distribution of CNTs in Al matrix. (30th April 2022) - Liu, Qibing; Fan, Genlian; Tan, Zhanqiu; Saba, Farhad; Guo, Qiang; Xiong, Dingbang; Su, Yishi; Li, Zhiqiang; Zhang, Di
Abstract: Controlling the location of carbon nanotubes (CNTs) within Al matrix is still challenging. To clarify the factors/mechanisms affecting the spatial distribution of CNTs, Short and Long CNTs were chosen as reinforcements, and their locations were characterized after ball milling, sintering and hot extrusion in order to study the effect of length-scale, thermal activation and external applied stress. The results showed that Long CNTs were only located at the grain boundaries (GBs). Differently, Short CNTs were mostly located at GBs when only external applied stress (ball milling) or thermal activation (sintering) is present, but entered grains with the synergy of thermal activation and external applied stress during thermomechanical process (hot extrusion). Based on the applied mathematical calculations, the main mechanism responsible for intragranular distribution of CNTs is the significant GB migration accelerated by thermal activation and external applied stress. The critical length for entering the CNTs in the grain interiors was calculated to be ∼103 nm, which agreed well with the experimental result (maximum length of ∼95 nm). The CNTs with the length larger than the critical value significantly decrease the velocities of themselves and GBs, and cannot be detached from GBs being still located at GBs in the Long CNT/Al composites. Graphical abstract: Image 1 Highlights: The evolution of spatial distribution of CNTs during ball milling, sintering and hot extrusion is investigated. Short CNTs enter grain interiors under the synergy of thermal activation and external applied stress during hot extrusion. The calculated critical length of CNTs for entering grains is ∼103 nm, which agrees well with experimental result (∼95 nm). Long CNTs simultaneously decrease the velocities of themselves and GBs, resulting in intergranular dispersion of CNTs.